Adaptation of Reactive Saccades is Influenced by Unconscious Priming of the Attention Focus. Issue 5 (3rd September 2017) - Bock, Otmar; Grigorova, Valentina; Ilieva-Staneva, Milena
ABSTRACT: The authors investigated whether the size of the attention focus can influence saccadic adaptation, and whether this influence changes in older age. Using the scrambled sentence task, young and older participants were either primed for a wide attention focus, or primed of a narrow attention focus, or were not primed for any specific attention focus. Subsequently, all participants underwent a double-step saccadic adaptation paradigm aimed at changing the direction of reflexive saccades. The authors found that compared to the nonprimed control group, priming for a wide attention focus enhanced saccadic adaptation in both age groups by a similar amount; the benefit persisted throughout the adaptation phase, but was absent during the deadaptation phase. In contrast, the authors found no effects of priming with a narrow attention focus on saccadic adaptation. From this the authors conclude that a wide attention focus is beneficial for workaround strategies but not for adaptive recalibration, and that those benefits are similar in young and older persons.